Analisis pengembangan materi IPS untuk meningkatkan hasil belajar siswa Kelas VII - Dewi Hartika, Eunike Br Simanjuntak, Febriana, Grace Michael Sihombing, Nisa Andriani Regar, Julia I (Journal of Educational Research and Humaniora (JERH), 2023)
One of the subjects taught is Social Sciences (IPS). IPS includes the study of social, economic, political, and geographical aspects. The main goal in the learning process is to achieve optimal learning outcomes in social studies subjects. However, students' learning outcomes in social studies are often not as expected. Several factors can cause this, including the lack of relevant and interesting material, ineffective teaching methods, and lack of interaction between students and the material being taught. The method used in this research is the literature study method where this literature study uses several references that can be used as guidelines in preparing articles. The teacher's role is very important in learning, because the teacher is responsible for guiding, planning, implementing, and evaluating learning. The teacher is also one of the determining factors for the success of learning. Therefore, it is important for teachers to integrate learning needs with learning objectives. To make learning easier for students, teachers can use various learning methods to convey subject matter. Using the right method can make it easier for students to acquire knowledge.